The m6A Methyltransferase METTL3 Is Functionally Implicated in DLBCL Development by Regulating m6A Modification in PEDF - Cheng, Yingying; Fu, Yuanyuan; Wang, Ying; Wang, Jinbi (Frontiers in Genetics, 2020)
Diffuse large B-cell lymphoma (DLBCL) is the most common subtype of lymphoma of which the treatment remains a major challenge to achieve the satisfactory curative effect. The underlying mechanisms also has not been fully illustrated. N6-Methyladenosine (m6A) has been identified as the most prevalent internal modification of mRNAs present in eukaryotes which is involved in the pathogenesis of cancers. it remains unclear how m6A mRNA methylation is functionally linked to pathogenesis of DLBCL. In this study, we sought to explore the roles of METTL3 on DLBCL development. The results showed that m6A level for RNA methylation and the expression level of METTL3 were up-regulated in DLBCL tissues and cell lines. Functionally, down-regulated METTL3 expression in DLBCL cells inhibited the cell proliferation ability. Further mechanism analysis indicated that METTL3 knockdown abates the m6A methylation and total mRNA level of Pigment Epithelium-Derived Factor (PEDF). However, Wnt/b-catenin signaling was not thus activated. Over-expressed PEDF abrogates the inhibition of cell proliferation in DLBCL cells that caused by METTL3 silence. In summary, above mentioned results demonstrated that the METTL3 promotes DLBCL progression by regulating the m6A level of PEDF.